Keharmonisan Keluarga Beda Agama (Studi Fenomena Keharmonisan Keluarga Beda Agama di Kecamatan Sindang Kelingi Kabupaten Rejang Lebong) - Mabrur Syah; Muhammad Arif Mustofa (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2020)
Expecting to have a family that harmonious and get along well is every family's dream. There are usually individual differences makes it a challenge for the realization of harmony in the family, but not for families in Sindang Kelingi. This study aims to describe the family harmony that occurs in Sindang Kelingi even though with different religions. This study is a descriptive qualitative research in the form of library research, with data collection then analyzed with descriptive data. The data on this Research was obtained through observation, interviews, and documentation. Results of this study are: Religious differences in families that occur in Sindang Kelingi village are formed by the pattern of parents and children. No religious differences were found with married couple andfamily harmony that has diversity in religion can be realized in Sindang Kelingi due to: there are of kinship, the sense of unity, the equality of work / profession of his parents (trans veterans), the advice from the elders to live in harmony, the village regulations for living in harmony and mutual respect the views of moderate religious leaders